Sentiment vs. Fundamentals: GMM Analysis of Jakarta Islamic Index during the 2020–2024 Crisis - Ahmad Yasin; Dewi Cahyani Pangestuti (JWM (JURNAL WAWASAN MANAJEMEN), 2026)
This study examines the impact of macroeconomic (BI Rate, Exchange Rate) and microeconomic factors (Current Ratio, Return on Equity) on the Jakarta Islamic Index (JII) during the 2020–2024 crisis period. Using System Generalized Method of Moments (GMM) on dynamic panel data , the study unexpectedly finds that all selected fundamental variables are statistically insignificant in explaining JII movements. These results indicate a "detachment" from fundamentals, where the Sharia market operated under a sentiment-dominated regime driven by systemic shocks, such as the COVID-19 pandemic and geopolitical tensions. The findings suggest that traditional fundamental analysis and conventional monetary instruments lose efficacy during periods of high collective psychological volatility.